Oral myiasis associated with drug induced gingival hyperplasia - a rare case report - Gadda Rohit B.; Agrawal Ankush; Kumar SN Santosh; Rothe Tushar Manohar (EDP Sciences, 2021)
Introduction: Myiasis (Greek: myi = fly) refers to infestation of living tissues of humans and animals by Dipterous eggs or larvae. Incidence of oral myiasis is comparatively lesser than that of cutaneous myiasis. We report a rare case of oral myiasis of anterior maxilla associated with drug induced gingival enlargement. Observation: We report a rare case of oral myiasis of anterior maxilla with amlodipine induced gingival enlargement in a sixty-two-year-old male with history of hypertension, hemiplegia and diabetes mellitus. Patient was mouth breather and presented with poor oral hygiene. Generalized gingival hyperplasia was observed. Multiple maggots were observed in the ulcerated areas on maxillary anterior alveolus. The maggots were mechanically removed with curettage after application of turpentine oil. Cleaning and debridement of the wound was done. After one month follow-up there was complete healing of the lesion. Maintenance of oral hygiene and gingivectomy as indicated was planned for this patient. Conclusion: Clinical significance of presented case is its rarity of association with drug induced gingival hyperplasia and typical presence of multiple predisposing factors. This case report provides interesting information about predisposing factors, clinical features and management of oral myiasis that could help clinicians in the diagnosis and management of this condition.